Translation Quality of Expressive Language in Poetry from English into Indonesian Made by English Department Students - Nadya Liza Syafitri; Havid Ardi (Journal of English Language Teaching, 2023)
This research aims at measuring students’ Translation Quality of Expressive Language in Poetry from English into Indonesian Made by English Department Students of Universitas Negeri Padang. The qualitative research was used in this research.  The population of this research was the sixth semester English Education students of Universitas Negeri Padang. There were 20 students selected as the sample through the purposive sampling method. Data were collected through a translation test. There were two raters involved in analyzing the quality of the translation result. Findings revealed that the translation quality produced by students are included as accurate with score 2.76, acceptable with score 2.66 and readable with score 2.73.